Nesting Technique as A Simple Method for Optimal Outcomes in Premature Infant Care: A Literature Review - Indartik Indartik; Nopi Nur Khasanah; Sri Wahyuni (Indonesian Journal of Global Health Research, 2025)
Preterm birth accounts for up to two-thirds of total cases worldwide. Premature infants often face challenges in adapting to life outside the womb due to immature organ development. Nesting is a method designed to create an environment resembling conditions in the womb by positioning the infant's body in a flexed posture and surrounding it with rolled cloth. This study aims to identify the physiological and psychological benefits of nesting while also providing evidence-based implementation guidelines for neonatal clinical practice. This study utilized a literature review design guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Article searches were conducted through electronic databases, including PubMed, Google Scholar, Crossref, OpenAlex, and Semantic Scholar. The search keywords used the Boolean operator (AND): "nesting AND preterm". Based on the review of 16 articles, the findings suggest that the nesting technique significantly contributes to improving physiological and behavioral parameters in premature infants. This technique provides numerous benefits, including enhanced vital stability, sleep quality, and neurobehavioral development. Overall, the nesting technique is an effective, safe, and easy-to-implement non-pharmacological method for improving the quality of care for premature infants. This intervention holds great potential to support physiological stability, sleep quality, and overall infant development.